Analisis Potensi Kebangkrutan Perusahaan Menggunakan Metode Altman Z-Score pada Perusahaan Sektor Property & Real Estate yang Terdaftar di BEI - Damara Krishnatama; Septarina Prita; S. Sudarno (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
Altman Z-Score is a method used to analyze the potential bankruptcy of a company. Z-Score is claimed to be able to detect corporate bankruptcy with a high degree of accuracy and this method was also very popularly used. Altman uses calculations through the five financial ratios in the formula, namely Net Working Capital to Total Assets, Retained Earning to Total Assets, Earning Before Interest and Taxes to Total Assets, Market Value of Equity to Book Value of Debt and Sales to Total Assets. On the consideration of the criteria for the selection of the object that has been determined, the researcher conducts research on 11 companies of Property & Real Estate sector listing on Indonesia Stock Exchange. This method classifies the condition of a company into 3 groups, namely crisis, gray area and healthy. The results of this study that has been done on 11 companies are 3 companies with crisis conditions, 4 companies with gray area conditions, and 4 companies with healthy conditions. Thus, it is expected for companies that are in crisis and gray area conditions to be more correction and can fix the existing problems in order to achieve the viability of a healthier company going forward. Keywords: Altman Z-Score, Bankruptcy, Financial Report, Property & Real Estate, Indonesia Stock Exchange (IDX)